Wohlers report : state of the industry annual worldwide progress report. - Wohlers, Terry T., ....- (Fort Collins : Wohlers, 2008)
Wohlers Report provides quantitative and qualitative analysis of additive fabrication (AF) worldwide. The technology encompasses a wide range of applications, including design review, concept modeling, prototyping, fit and function testing, pattern making, and tooling. A growing number of companies are using AF to manufacture products-or parts that going into products-that are difficult, impossible, or too expensive to produce any other way. The report covers the growing range of applications and technologies, as well as the challenges that organizations face when trying to understand and make use of this fast-developing technology. The report was developed with support from 53 co-authors, 58 service providers, 26 system manufacturers, and many others worldwide. To support the review and analysis, the softbound publication includes 31 charts and graphs, 44 tables, 138 photographs and illustrations, and eight appendices. This study, published for 13 consecutive years, has established a
Tradition of covering all facets of additive fabrication, including business, product, market, technology, research, and application. Wohlers Report 2008 addresses many facets of additive fabrication, including its history, the wide mix of applications, the industries embracing the technology, annual revenues from products and services, growth estimates, sales forecasts, and investor information. It also provides current information on service providers and system manufacturers, as well as cast metal parts, direct metal fabrication, advanced approaches to tooling, and exciting new applications of rapid manufacturing. The study reports on new developments in the U.S., Europe, Asia, and other parts of the world, documents the growth of CAD solid modeling, follows the advances in the materials used for additive processes, highlights opportunities in medical modeling, and lists applications and technologies for 3D scanning and reverse engineering. The final parts of the report cover emerging
Technologies, government-sponsored research and development, and college and university education and research. Wohlers Report 2008 concludes with a discussion on the future of additive fabrication-where it is headed and what to expect-to assist in strategic planning and investing.
Keywords: Technologie ; toekomst